Studio photography - Child, John (Essential skills., 2005)
John Child has refreshed and updated his inspirational studio photography guide to cover all the latest techniques. Now beautifully illustrated in full colour, featuring brand new student and author work, Studio Photography guides you through the techniques you need to create successful studio images. Through a clearly structured learning approach, you will stimulate and express your creative ideas using a wide variety of activities and assignments. With a strong commercial orientation, the emphasis is highly practical and focuses on technique, communication and.